Late Follicular Phase Ovarian Stimulation Without Exogenous Pituitary Modulators - Zhu, Xiuxian; Ye, Jing; Fu, Yonglun (Frontiers in Endocrinology, 2020)
Introduction: A gonadotropin-releasing hormone antagonist is the most common modulator used to prevent the premature luteinizing hormone (LH) surge when ovarian stimulation was initiated in the late follicular phase. We aimed in this study to evaluate the feasibility of performing ovarian stimulation in the late follicular phase without the use of exogenous pituitary modulators. Methods: Data were retrospectively collected from 404 normo-ovulatory patients who underwent their first in vitro fertilization (IVF)/intracytoplasmic sperm injection (ICSI) treatment in our department. One hundred sixteen subjects in the study group received ovarian stimulation when a dominant follicular diameter of ≥ 10 mm was confirmed by transvaginal ultrasonography after menstrual cycle day 6, which entailed a daily injection of gonadotropin until the trigger day, while 288 subjects in the control group received ovarian stimulation in the early follicular phase under a progesterone protocol. The primary outcome was the number of mature oocytes. Results: There was no statistical difference in the number of mature oocytes between the two groups (9.67 ± 5.33 in the study group vs. 9.38 ± 5.15 in the control group, P = 0.693). No secondary LH surges in the study group and no premature LH surges in the control group were found during ovarian stimulation. The good-quality embryo rate per oocytes retrieved showed no significant difference between the two groups (35.22% vs. 35.91%, P =0.665). The clinical pregnancy rate per transfer was 54.55% in the study group and 56.48% in the control group (P = 0.718), and the implantation rate was similar between the two groups (36.94% vs. 37.77%, P = 0.829). Conclusions: Our study revealed that late follicular phase ovarian stimulation could be performed without an exogenous pituitary modulator.